Response to: Dittrich et al.: Non-Embryo-Destructive Extraction of Pluripotent Embryonic Stem Cells – Overlooked Legal Prohibitions, Professional Legal Consequences and Inconsistencies in Patent Law - Faltus, T.; Storz, U. (Geburtshilfe und Frauenheilkunde, 2016)
The publication of “Non-embryo-destructive Extraction of Pluripotent Embryonic Stem Cells: Implications for Regenerative Medicine and Reproductive Medicine” by Dittrich et al. in Geburtshilfe und Frauenheilkunde 2015; 75: 1239–12421 describes various possibilities which could result from the non-embryo-destructive extraction of embryonic stem cells from human blastocysts. But implementing this method is more problematic, both legally and ethically, than the authors have represented it to be and is illegal in Germany. German patent DE 10 2004 062 184 on the non-embryo-destructive extraction of embryonic stem cells referred to by Dittrich et al. contravenes the higher-ranking case-law of the European Court of Justice. Ultimately, the non-embryo-destructive harvesting of embryonic stem cells with the aim of storing these cells for use in potential therapies as proposed by Dittrich et al. is prohibited in Germany and could lead to criminal prosecution.
Keywords: stem cell extraction; non-embryo-destructive; pre-implantation genetic diagnosis (PIGD); stem cell patent